Analysis of the Effect of Sustainable Marketing Strategy, Brand Image, and Customer Satisfaction on Customer Loyalty in the Manufacturing Industry in Karawang - Sudirjo, Frans; Mu'min, Halek; Marjuki, Marjuki; Triyantoro , Andri (West Science Interdisciplinary Studies, 2024)
This research investigates the dynamics of Sustainable Marketing Strategy, Brand Image, Customer Satisfaction, and their collective impact on Customer Loyalty in the manufacturing industry in Karawang. A quantitative analysis, employing Structural Equation Modeling (SEM-PLS), was conducted on a sample of 250 manufacturing firms. The results reveal statistically significant relationships: Sustainable Marketing Strategy positively influences Brand Image, Customer Satisfaction, and ultimately, Customer Loyalty. Brand Image and Customer Satisfaction also exhibit direct positive impacts on Customer Loyalty. The findings offer strategic insights for firms to navigate the competitive landscape by emphasizing sustainable practices, brand building, and a customer-centric approach. Policymakers can leverage these insights to advocate for sustainable development within the manufacturing sector, contributing to both economic and environmental sustainability.